Dynamics of Social Interaction and Survival Strategies in the Prostitute Community in Bungurasih Surabaya - ALFARISI, M. SALMAN; Nugroho, Agung; Handoyo, Pambudi (Jurnal Paradigma, 2024)
The prostitute industry has long been a subject of research interest in the social, economic, and cultural contexts of various regions around the world. In Indonesia, especially in the Bungurasih area of Surabaya, the existence of the prostitute community raises various important questions regarding social dynamics, survival strategies, and the welfare conditions of the individuals involved in it. Therefore, the aim of this research is to understand the dynamics of socio-economic life and to find out the survival strategies of prostitutes in Bungurasih Surabaya. This research uses the theory of symbolic interactionism proposed by George Herbert Mead. This research uses qualitative research methods, with data collection techniques in the form of literature studies and field studies, which contain two techniques, namely observation and interviews. The results of this research show that the dynamics of social interactions in the prostitute community are very complex and involve various parties, including fellow prostitutes, pimps, law enforcement officers, and the surrounding community. These relationships can be cooperative or competitive and are often influenced by economic factors and social controls. The prostitutes must overcome significant social stigma and discrimination, which can impact their psychological and emotional well-being.